The State of Access to Modern Energy Cooking Services - Energy Sector Management Assistance Program (World Bank, Washington, DC, 2020)
Progress towards ensuring access to modern cooking solutions, a key component to achieving Sustainable Development Goal 7 (SDG 7), has been slow. Today, 2.8 billion people globally still cook with traditional polluting fuels and technologies, costing the world more than 2.4 trillion dollars each year, driven by adverse impacts on health (1.4 trillion dollars), climate (0.2 trillion dollars), and women (0.8 trillion dollars from lost productivity). Solutions to tackle this pressing development challenge must prioritize user preferences and local cooking contexts to address longstanding barriers to the adoption of modern cooking solutions. The report finds that four billion people around the world still lack access to clean, efficient, convenient, safe, reliable, and affordable cooking energy. To achieve universal access to modern energy cooking services (MECS) by 2030, it calls for actions to prioritize MECS access in global and national arenas, formalize cooking energy demand in national energy planning, and dramatically scale up public and private financing.